Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Pada Pt Amanah Garment Internasional - Retno Wulandari; Hasim As’ari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Retno Wulandari, 2023 The Influence of Good Corporate Governance on Financial Performance at PT Amanah Garment International. Thesis for the Accounting study program, Faculty of Economics, Mercu Buana University, Yogyakarta (supervised by Mr. Hasim As'ari, S.E., M.M).This research aims to analyze and determine the influence of Good Corporate Governance on Financial Performance at PT Amanah Garment International. The research was conducted from May to June 2023. The population of this study consisted of employees in the finance and corporate departments of PT Amanah Garment International. The sample size taken for this research was 49 individuals. The data will be analyzed using multiple linear regression.